Pendampingan Pengembangan UMKM dengan Transformasi ke Bisnis Syariah : Pengurusan NIB & Pembiayaan Pelaku UMKM Kota Padang - Fitri, Radia; Afriyanti, Afriyanti; Ulyadi, Ulyadi (Jurnal Pengabdian UNDIKMA, 2024)
This service aimsÂ to increase the understanding of UMKM players regarding the development of UMKM with their transformation into sharia business.Â UnderstandingÂ ShariaÂ business was focused on anti-usuryÂ ShariaÂ financing.Â Apart from understanding financing, they were also assisted in issuing NIB and financing to Islamic banking institutions.Â The method of this service was Participatory Action Research (PAR),Â whereÂ the team accompanies Padang City UMKMÂ (Micro, SmallÂ and Medium Enterprises)Â actors.Â Evaluation was carried out by sharing experiences from UMKM actors, feedback, and follow-up. Data analysis used in this service used descriptive analysis.Â The success of this activity was measuredÂ byÂ the understanding provided to UMKM actors regardingÂ the ShariaÂ business.Â The results of this service showed that UMKM actorsÂ understoodÂ ShariaÂ business principles; UMKM actors proved this: 1) Wanting to switch to aÂ ShariaÂ institution in accordance with applicable regulations, 2) Registering as Nagari Syariah bank customers, 3) Registering their business to get NIB because including the requirements for financing files and processing halal certificates, 4) Registering the business to obtain Sharia capital, 5) Filling in the halal certificate issuance form to obtain a halal certificate.